AMP – a novel architecture for IP-based Mobility management - Wan Hazlina, Hassan; Hassan Abdalla Hashim, Aisha; Norsheila , Fisal (IJCSNS, 2008)
In this research, an architecture called the Agent-based Mobility Protocol (AMP) comprising a multi-agent system residing in both the mobile host(s) and the access networks has been developed for the purpose of enhancing mobility management in IP-based networks. The agent system on the mobile host was designed and subsequently built using an agent development platform called Agent Builder Pro. The core of the AMP architecture is the access network agency and both its specifications and the corresponding mobility management were designed using a combination of collaboration and operation diagrams. Given the scope and complexity of computer networks generally, and the Internet, specifically, the use of a network simulator was considered appropriate in providing a wider and comprehensive understanding of how the AMP architecture and protocol would perform in supporting a mobile host roaming over multiple network domains or autonomous systems. Hence, this paper presents our work in developing the AMP architecture including its implementation over a discrete-event network simulator called ns-2 where customized objects have been built into the simulator. In addition, using different simulated scenarios, the architecture and protocol operations of AMP for mobility management were evaluated against Mobile IP as a basis for comparative analyses.